Faktor-Faktor yang Mempengaruhi Loyalitas Pengguna Aplikasi BYOND: Peran Mediasi Kepuasan Nasabah Bank BSI - Moh Zaky Fakhrezy; Rini Safitri (Commodities, Journal of Economic and Business, 2026)
Progress in digital technologies across the banking industry has reshaped consumer patterns in adopting electronic financial services, encompassing Islamic banking domains. The present investigation examines the linkage between digital service quality and perceived ease of use with loyalty among BYOND app users, positioning customer satisfaction as the intervening factor. Employing a quantitative methodology, the study targets Bank BSI clientele in Malang City, drawing a purposive sample of 115 participants. Primary data were gathered via Likert-scale questionnaires and subjected to analysis through Structural Equation Modeling (SEM) employing the Partial Least Squares (PLS) approach within SmartPLS 4.1.1.8 software. Findings reveal that both digital service quality and ease of use exert a significant positive effect on customer loyalty. Customer satisfaction effectively mediates this association. These outcomes underscore that enhancements in digital service standards and app accessibility can elevate satisfaction levels, thereby bolstering loyalty. Thus, prioritizing user-centric digital service innovations emerges as a pivotal tactic for enhancing the competitive edge of Islamic banking amid the digital transformation.